Past distribution and ecology of the cork oak (Quercus suber) in the Iberian Peninsula: a pollen-analytical approach - Carrión, J. S.; Parra, I.; Navarro, C.; Munuera, M. (Diversity and Distributions, 2000)
This study presents pollen-analytical data from continental and offshore Iberian Peninsula sites that include pollen curves of Quercus suber, to provide information on the past distribution and ecology of the cork oak (Q. suber). Results centre on a new pollen record of Navarrés (Valencia, eastern Spain), which shows that the cork oak survived regionally during the Upper Pleistocene and was important during a mid-Holocene replacement of a local pine forest by Quercus-dominated communities. This phenomenon appears linked to the recurrence of ﬁre and reinforces the value of the cork oak for reforestation programmes in ﬁre-prone areas. In addition to Navarrés, other Late Quaternary pollen sequences (Sobrestany, CasablancaAlmenara, Padul, SU 8103, SU8113, 8057B) suggest last glacial survival of the cork oak in southern and coastal areas of the Peninsula and North Africa. Important developments also occur from the Late Glacial to the middle Holocene, not only in the west but also in the eastern Peninsula. It is suggested that, in the absence of human inﬂuence, Q. suber would develop in non-monospeciﬁc forests, sharing the arboreal stratum both with other sclerophyllous and deciduous Quercus and Pinus species
Keywords: Cork oak; historical biogeography; iberian peninsula; palaeoecology; pollen.

Past distribution and ecology of the cork oak (Quercus suber) in the Iberian Peninsula: a pollen-analytical approach - Carrión, J S; Parra, I; Navarro, C; Munuera, M (Diversity and Distributions, 2000)
This study presents pollen-analytical data from continental and offshore Iberian Peninsula sites that include pollen curves of Quercus suber, to provide information on the past distribution and ecology of the cork oak (Q. suber). Results centre on a new pollen record of Navarrés (Valencia, eastern Spain), which shows that the cork oak survived regionally during the Upper Pleistocene and was important during a mid-Holocene replacement of a local pine forest by Quercus-dominated communities. This phenomenon appears linked to the recurrence of ﬁre and reinforces the value of the cork oak for reforestation programmes in ﬁre-prone areas. In addition to Navarrés, other Late Quaternary pollen sequences (Sobrestany, CasablancaAlmenara, Padul, SU 8103, SU8113, 8057B) suggest last glacial survival of the cork oak in southern and coastal areas of the Peninsula and North Africa. Important developments also occur from the Late Glacial to the middle Holocene, not only in the west but also in the eastern Peninsula. It is suggested that, in the absence of human inﬂuence, Q. suber would develop in non-monospeciﬁc forests, sharing the arboreal stratum both with other sclerophyllous and deciduous Quercus and Pinus species
Keywords: Cork oak; historical biogeography; iberian peninsula; palaeoecology; pollen.